2014
DOI: 10.1038/ejhg.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

Progressive hearing loss and vestibular dysfunction caused by a homozygous nonsense mutation in CLIC5

Abstract: In a consanguineous Turkish family diagnosed with autosomal recessive nonsyndromic hearing impairment (arNSHI), a homozygous region of 47.4 Mb was shared by the two affected siblings on chromosome 6p21.1-q15. This region contains 247 genes including the known deafness gene MYO6. No pathogenic variants were found in MYO6, neither with sequence analysis of the coding region and splice sites nor with mRNA analysis. Subsequent candidate gene evaluation revealed CLIC5 as an excellent candidate gene. The orthologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…These data thus suggest that CLIC5 is required for the development and/or maintenance of glomerular endothelial cells and podocyte architecture. Consistent with this, a recent study has shown that a patient with a homozygous nonsense mutation in CLIC5 has mild renal dysfunction in addition to hearing loss (Seco et al, 2015).…”
Section: Clic5supporting
confidence: 63%
See 2 more Smart Citations
“…These data thus suggest that CLIC5 is required for the development and/or maintenance of glomerular endothelial cells and podocyte architecture. Consistent with this, a recent study has shown that a patient with a homozygous nonsense mutation in CLIC5 has mild renal dysfunction in addition to hearing loss (Seco et al, 2015).…”
Section: Clic5supporting
confidence: 63%
“…Mutation analysis in humans has shown that CLIC5 is involved in progressive hearing impairment and vestibular dysfunction (Seco et al, 2015). In mouse, renal glomeruli in CLIC5-deficient mice exhibit reduced ezrin levels, broadened podocyte foot processes, as well as large vacuoles in glomerular endothelial cells that can lead to renal dysfunction under unfavorable genetic or environmental conditions (Wegner et al, 2010).…”
Section: Clic5mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015 and the first half of 2016, for instance, 14 additional genes were identified as causing NSHL in humans [417,18*], increasing the number of NSHL genes to nearly 100 (http://www.hereditaryhearingloss.org). Prior to TGE+MPS, the best genetic diagnosis for NSHL required serial gene-by-gene Sanger sequencing, a constraint that made comprehensive diagnostic testing prohibitively slow and expensive.…”
Section: Tge+mps In Hearing Loss Diagnosis and Available Testing Optionsmentioning
confidence: 99%
“…Many genes have been described to be involved in only one or a few families with HI. [3][4][5] Some exceptions are known, for example, mutations in GJB2 followed by mutations in STRC and MYO15A are the most common causes for arNSHI worldwide. [6][7][8][9] Since many genes contribute to hereditary HI, targeting all or a selection of protein-coding exons in a single experiment, as in WES, might currently be the best option for a comprehensive genetic analysis of HI individuals.…”
Section: Introductionmentioning
confidence: 99%